Beban Kognitif Siswa Dalam Pembelajaran BerdasarkanKurikulum Merdeka Sekolah Dasar - Mohammad Habibie Zarkasyi; Zainul Abidin; Henry Praherdhiono (Journal of Educational Technology Studies and Applied Research, 2024)
Cognitive Load is a theory that describes the amount of mental resources a person uses to complete a learning task. Mental resources are a person's cognitive abilities including mind, attention, memory and problem solving skills. Cognitive load in learning that occurs in the classroom describes the condition of students in dealing with learning tasks. The independent curriculum is the curriculum currently used at all levels of education including primary education. However, the curriculum faces problems both in terms of teachers and learners. The purpose of this study was to describe the condition of intrinsic, extrinsic and germane cognitive load of students during learning when using an independent curriculum. This research uses a descriptive qualitative approach. The data collection technique used purposive sampling as many as 6 informants consisting of 2 teachers and 4 students. The results of this study are the intrinsic cognitive load of students found in IPAS, PPKN, Mathematics, English and Javanese subjects. In addition, the intrinsic cognitive load is triggered by giving assignments and motivation or interest in learning from the students themselves. Extrinsic cognitive load was triggered by the lecture learning method used by the instructor or teacher due to the use of high vocabulary. Extrinsic cognitive load is also triggered by the condition of the learning environment, namely the noisy or crowded atmosphere inside and outside the classroom. The germane cognitive load is triggered when the teacher or lecturer presents the subject matter.